(untitled) (INTI Nusa Mandiri, 2025)
In today’s digital era, chatbots have become an essential tool for businesses to improve interaction with customers. A responsive and efficient chatbot can help customer service agents be happier, improve customer satisfaction, and resolve issues faster. The study aims to create a Telegram-based chatbot that uses the Random Forest algorithm and the Word2Vec method to answer questions about ICT services. The development was carried out by collecting a dataset of questions and answers from FAQs (Frequently Asked Questions) of ICT services. Then, the Random Forest algorithm is used to classify the questions. In addition, the Word2Vec method is used to create vector representations of words in questions and answers. This improves the chatbot’s ability to understand complex questions. The test results show that the chatbot gets an accuracy of 91.28%, a precision of 93.56%, a recall of 91.28% and an F1-Score of 91.42% and can provide relevant and accurate answers to user questions. Therefore, the development of this chatbot using the Random Forest algorithm and the Word2Vec method can be an effective solution to improve customer service in the field of ICT services